Barriers to and facilitators of timely family consent in caesarean sections: Experiences, perspectives and associated factors–a mixed-methods study in Somaliland - Jonah Kiruja; Fatumo Osman; Helena Litorp; Jama Ali Egal; Amina Esse; Marie Klingberg-Allvin (PLoS ONE, 2026)
Introduction In many countries, the consent for caesarean section (CS), when indicated, is made by the woman herself. However, in Somaliland, the family (husband, father, or other close male family member) are required to make the consent for CS to be performed, a process that can be time-consuming and result in adverse outcomes. This study aimed to investigate the barriers to and facilitators of timely family consent in caesarean sections at the national referral hospital in Somaliland. Methodology A convergent mixed-methods study with a parallel sampling method was conducted at the national referral hospital in Somaliland. Quantitative data was collected on timely vs. late family consent for CS, as well as sociodemographic and obstetric characteristics. Data were analysed using binary and multivariable logistic regression. In addition, in-depth interviews were conducted and analysed using thematic analysis. Results Of the 516 women included in the quantitative phase of the study, 16 participated in the in-depth interviews. The quantitative results showed that women with hypertensive disorders (aOR 8.491; 95% 1.076–66.991) and obstetric haemorrhage (aOR 3.209; 95% CI 1.159–8.887) had higher odds of late family consent compared to women without hypertensive disorders and obstetric haemorrhage respectively. The themes that emerged on barriers to timely family consent for CS were poor communication and understanding, delayed informed choice for CS, differences in understanding between family members on the indication for CS, and absence of the person providing formal consent. The themes that emerged on facilitators of timely family consent were the husband’s autonomous decision making for CS and adequate disclosure of all relevant information about CS. Conclusion A standard counselling package can be designed on educating family members on the importance of timely CS consent during the antenatal period with male involvement. A policy should be developed that gives women the autonomy to make health decisions and give consent in maternal health emergencies. Healthcare providers need training on effective communication when requesting CS consent, with a focus on the elements of informed consent.